2001
DOI: 10.1093/gerona/56.4.m200
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Enhancement of Food Improves Dietary Intake and Nutritional Status of Elderly Nursing Home Residents

Abstract: Adding flavor enhancers to the cooked meals was an effective way to improve dietary intake and body weight in elderly nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(121 citation statements)
references
References 24 publications
4
112
0
5
Order By: Relevance
“…The authors observed no increase in intake by the groups who received flavoring or MSG added to their food over 16 weeks. Other studies (Mathey et al, 2001;Schiffman and Warwick, 1993) have shown that flavor enhancement does increase intake in elderly subjects, but attribute their original diminished intake to a decline in flavor perception. Since our rats presumably have intact flavor perception, these studies may not be comparable.…”
Section: Discussionmentioning
confidence: 97%
“…The authors observed no increase in intake by the groups who received flavoring or MSG added to their food over 16 weeks. Other studies (Mathey et al, 2001;Schiffman and Warwick, 1993) have shown that flavor enhancement does increase intake in elderly subjects, but attribute their original diminished intake to a decline in flavor perception. Since our rats presumably have intact flavor perception, these studies may not be comparable.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that improving flavor of foods can improve nutritional intake and body weight in nursing-home patients. 38 The role of cytokines has been discussed earlier. Circulating levels of IL1, IL6 and TNFα have been shown to be higher in older people and associated with reduced muscle mass.…”
Section: Physiological Anorexiamentioning
confidence: 97%
“…Both of these studies were cross-sectional and were limited by their relatively small sample size. Mathey et al (2001) evaluated the impact of flavor-enhancers in a nursing home population. Energy intake declined in the control group but remained stable in the intervention group.…”
Section: (3):291-300 (2002)mentioning
confidence: 99%